KULIT BUAH JERUK LIMAU (Citrus amblycarpa (Hassk.) Osche) SEBAGAI ANALGESIK - Maharani, R. A. I. K.; Cahyaningsih, N. K.; Abimanyu, M. D.; Astuti, K. W. (Jurnal Kimia (Journal of Chemistry), 2020)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the treatment options for relieving pain. However, long-term use can trigger gastrointestinal bleeding. Therefore, alternative analgesics which have the same therapeutic effect with lower side effects are needed. Limau ( Citrus amblycarpa ) is an empirical drug for tingling and cramping. The aim of the study is to determine the analgesic activity of ethanol extract of C. amblycarpa fruit peel. The method used in testing analgesic activity is the Hot Plate method. The study was conducted by dividing 30 mice into 6 groups. The group given CMC-Na 1% was used as a negative control, the group given suspension of sodium diclofenac dose of 6.5 mg/kg of body weight was used as a positive control, and the group given suspension of ethanol extract of C. amblycarp a fruit peel with dose variations 100, 300 and 600 mg/kg of body weight. The test animals were placed on top of the Hot Plate with a temperature of 70°C at 30 minutes after giving suspension test and the response time of mice to heat was observed every 30 minutes for 3 hours with cut off time 15 second. Based on the test results, it can be concluded that the administration of ethanol extract of C. amblycarp a fruit peel with 100, 300 and 600 mg/kg of body weight gave analgesic activity on mice compared to the negative controls (CMC-Na 1%).   Keywords : C. amblycarpa , Fruit Peel, Analgesics, Hot Plate